HUBUNGAN MINDFULNESS DAN VIGOR DENGAN PRESTASI AKADEMIK PADA MAHASISWA DI UNIVERSITAS X - Mutiara Mirah Yunita; Teguh Lesmana (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2019)
The data shows that some students have experienced failure in lectures and failures in lectures that have an impact on dropping out of college need to be found. One of the initial factors that contributed to failure in lectures was a low GPA. Students need to have a way to have a positive learning attitude so that they can contribute to improving their GPA. In this case the researcher aims to find out the role of mindfulness and vigor on the student GPA, in addition to finding out the relationship between mindfulness and vigor. The method used in this study is the correlation analysis technique to find evidence of the relationship of mindfulness with vigor, and academic achievement. The number of samples used was 81 students from University X. Mindfulness was measured using the Five Facet Mindfulness Questionnaires (FFMQ), vigor was measured using the Shirom-Melamed vigor measure (SMVM) and academic achievement was measured by student GPA. Both measuring instruments have been adapted into Indonesian, and have good reliability based on the trial process. The results of this study indicate that there is a relationship between mindfulness and vigor. Other analysis results also show that there is a significant relationship between mindfulness and vigor with academic achievement in students.